Clinical workflow of two different CAD/CAM systems for veneers manufacture - Jurado, Carlos Alberto; Mourad, Firas; Felton, David; Tinoco, Jose Villalobos (European Journal of General Dentistry, 2020)
Digital technology is improving dentistry by manufacturing restorations faster and easier. Veneers can be handcrafted fabricated by the dental technician or designed by software and fabricated by a milling machine. Currently, there are many scanners available in the market that are clinically acceptable for the fabrication of restorations. However, there have been no clinical reports comparing the clinical protocols of the two most frequently used software programs in the market. The aim of this article is to show the digital workflow of the two most common systems for the fabrication of CAD/CAM veneers.
Keywords: CADCAM; digital dentistry; esthetic dentistry; scanners; technology; veneers